Institusi Riset dan Keilmuan Islam Masa Klasik - M. Iqbal Dawami (TASAMUH: Jurnal Studi Islam, 2016)
Muslims responded to the commands of the Prophet to study very much. The time of the Prophet s.a.w. is already growing efforts of informal education, which puts the mosque as educational institutions.The education system in the mosque and then developed into a madrasa system, known as formal education institutions to transfer the Islamic religious sciences. Non-religious sciences are transferred through informal education. In the past year Abasiyah Bani 750-848 AD, is one of the holders of the rulers of Muslim rule very concerned about science, then became the driving growth of Islamic education. From that moment the Muslims had not made a dichotomy between religious and non-religious sciences. For instance, the establishment of an Academy of Yundi Shapur in Persia Southeast not only makes scientific works, philosophy and translations into language Pahlavi, but also in medicine, mathematics, astronomy, and anyway become a center of research institutes and knowledge centers.